URBAN SUFISM: A CASE STUDY OF TASAWUF PRACTICES IN THE UICCI STUDENTS OF SULAIMANIYAH CIPUTAT - Muhammad Akmal Falah (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
The phenomenon of the emergence of a higher interest in studying religious knowledge with a spiritual path began to develop in society. This cannot be separated from the role of the tarekat in the midst of urban life. People in urban areas who study religious knowledge and learn about Sufism in urban areas are then better known as "urban Sufism". The existence of an institution that facilitates students who want to explore religious knowledge while learning Sufism, UICCI Islamic Boarding School branch Sulaimaiyah Ciputat, located in Ciputat, South Tangerang, is a place for Muslim students who want to study religious knowledge and also Sufism. Most students in this pesantren are students from various fields and majors from various universities which are dominated by UIN Jakarta students. This pesantren has its own privileges compared to several other pesantren around it, namely that they practice the teachings of Sufism with the Naqsyabandiyah order as its basic foundation.